Effectiveness and safety of oral versus intravenous iron therapy in iron deficiency anemia during pregnancy: A pharmacological review - Reny Haryani; Juwana Janu (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Iron deficiency anemia is a global health problem commonly occurring during pregnancy. The World Health Organization reported a prevalence of 35.5% in 2023, which may lead to serious consequences for both mother and fetus. Management of this condition is generally carried out through oral or intravenous iron therapy, each having its own advantages and limitations. Purpose: to evaluate the effectiveness and safety of oral versus intravenous iron therapy in pregnant women with iron deficiency anemia. Method: A limited systematic review was conducted based on PRISMA guidelines. Literature searching was performed using the PubMed database for studies published between 2015 and 2025. A total of 75 articles were identified, of which 5 studies met the inclusion criteria and were analyzed descriptively. Results: The findings showed that intravenous iron therapy, particularly ferric carboxymaltose, was more effective in increasing hemoglobin and ferritin levels compared to oral therapy. In terms of safety, oral iron was more frequently associated with gastrointestinal side effects, whereas intravenous iron was generally well tolerated with mild adverse effects. Conclusion: Intravenous iron therapy demonstrates superior effectiveness in improving hematological parameters; however, oral iron remains the first-line therapy due to its accessibility and lower cost. Therefore, treatment selection should be individualized based on the patient’s clinical condition.